Solvent extraction of uranium from an acidic medium for the front-end of nuclear fuel cycle: from mechanisms understanding to innovative process design - Giusti, Fabrice; Guerinoni, Elise; Lemire, David; Thimotée, Marine; Arrachart, Guilhem; Dourdain, Sandrine; Pellet-Rostaing, Stéphane (Comptes Rendus. Chimie)
Despite the fact that methods for uranium extraction from an acidic medium (sulfuric, phosphoric or nitric) are relatively robust processes, the search for more efficient systems in terms of extraction efficiency and selectivity with respect to competitor ions remains relevant. To address this challenge, researchers have developed a wide range of new extracting molecular agents that allow efficient and selective liquid–liquid extraction of the target metal. After delivering a synoptic reminder of the former hydrometallurgical processes on which dogmas have been based, we present an exhaustive report of the structures that have been designed, synthesized and evaluated as useful hydrometallurgical tools for the extraction of uranium focused on the front-end of the nuclear fuel cycle. Moreover, peculiar emphasis has been given to theoretical aspects related to parameters, such as amphiphilic properties, which influence the extraction mechanism involved in each system, be it mono- or multifunctional ligand. Concluding remarks were afforded as consistent milestones of a prospective and promising route for the next hydrometallurgy including the influence of the stereochemistry.